Using mobile phones to promote maternal and child health: knowledge and attitudes of primary health care providers in southwest Nigeria - Mobolanle R Balogun; Godfred O Boateng; Yenupini J Adams; Bukola Ransome-Kuti; Adekemi Sekoni; Ellis A Adams (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background The use of mHealth by primary health care providers is a unique opportunity to improve maternal and child health in Sub-Saharan Africa. However, few studies have examined the effects of primary health care providers' knowledge and attitudes of mHealth for maternal and child health promotion in low-resource settings. Therefore, this study assesses the knowledge and attitudes of primary health care providers on the use of mobile technologies such as internet-enabled smartphones for maternal and child health services. # Methods We used data from a cross-sectional study of seven urban local government areas in Lagos, Nigeria. A total of 518 primary health care providers were surveyed for information on the use of mobile technologies, attitudes, and actual use of mobile technologies for maternal and child health services. Data were analyzed using descriptive and multivariable linear and logistic regression models. # Results Our study showed that smartphone ownership is not a predictor of high mHealth knowledge; however, having an internet-enabled smart phone was a strong predictor of higher knowledge of mHealth (regression coefficient, ß=1.20, 95% confidence interval, CI=0.61-1.79) among primary health care providers. Owning a smartphone (ß=1.00, 95% CI=0.12-1.89) and having internet-enabled phone (ß=1.14, 95% CI=0.18-2.10) were both predictors of positive mHealth attitude. Primary health care providers with higher scores on mHealth knowledge were 1.32 times more likely to use mHealth for maternal and child health services. Similarly, those with positive attitude towards mHealth were 1.15 times more likely to use mobile technology for maternal and child health services. # Conclusion The results suggest the use of mHealth tools by primary health care providers to render maternal and child health services is affected by their knowledge and attitude towards mHealth. Interventions that focus on increasing mobile technologies with internet enabled devices like smartphones are needed to improve knowledge, attitudes, and use of mHealth in maternal and child health services.